Development and validation of screening tools for classification consumers of food products based on eating healthy criteria - Soontrunnarudrungsri, Aussama (Kansas State University, 2011)
Because healthy food products do not have a specific tool used for consumer screening based on consumers’ diet or degree of healthy eating habits, this study aimed to determine a set of questions that could classify consumers who belong in a different status according to the Stages of Change model, including those who have a different diet quality based on their Healthy Eating Index (HEI) score. The surveys were conducted in the United States (US) and Thailand in order to determine applicability to varying countries. The Food Neophobia Scale (FNS), Food Involvement Scale (FIS), and Health and Taste Attitude Scale (HTAS) were included in the questionnaire together with a set of Stages of Change questions and a 7-day, self-administered food recall questionnaire. The HEI interpretation of US and Thai consumer scores illustrated that the majority of both belonged to the Need Improvement group. The Stages of Change model indicated most consumers thought they had healthy diets. According to FNS, FIS, and HTAS, US consumers are more involved in food activities and are more open to trying new foods or unfamiliar foods than Thais. Furthermore, consumers who belong in different groups, according to the Stages of Change model, responded differently to some HTAS subscales. However, statements from FNS, FIS, and HTAS were not capable of distinguishing consumers belonging in different groups according to HEI scores or belonging in different stages according to the Stages of Change Model. Considering all possible methods from those listed above for screening consumers, the Stages of Change model may be the best way to segment consumers interested in healthier eating. Using the Stages of Change required less time and the least effort from consumers because there were only three questions; and interpreting results does not require calculation or analysis.
Keywords: Consumer Behavior; Eating Behavior; Stages of Change Model; Food Related Psychographic Scale; Dietary Assessment; Screening Consumer; Food Science (0359); Nutrition (0570)